2002
DOI: 10.1007/s00210-002-0585-3
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation and potentiation of cGMP-mediated response by ibudilast in bovine tracheal smooth muscle

Abstract: The effects of ibudilast, an inhibitor of phosphodiesterases (PDEs), on tension, levels of guanosine 3',5'-cyclic monophosphate (cGMP) and adenosine 3',5'-cyclic monophosphate (cAMP) were investigated in bovine tracheal smooth muscle. We especially examined the combined effect of ibudilast with the cGMP-elevating agents on these parameters. Ibudilast was equipotent to attenuate the precontractions induced by both 0.3 microM methacholine and 40 mM K(+). By contrast, the relaxant effects of sodium nitroprusside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Endothelium-derived nitric oxide produced under basal conditions or by a stimulus readily diffuses into the contiguous smooth muscle to activate soluble guanylyl cyclase, resulting in increased cGMP synthesis and smooth muscle relaxation (Ignarro, 1990;Nakahara et al, 2002;Gao et al, 2004). Nitric oxide (NO), a potent vasodilator in the pulmonary circulation, is important in the transition of the pulmonary circulation from fetal to postnatal life.…”
Section: Cyclic Nucleotides and Pafr-mediated Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelium-derived nitric oxide produced under basal conditions or by a stimulus readily diffuses into the contiguous smooth muscle to activate soluble guanylyl cyclase, resulting in increased cGMP synthesis and smooth muscle relaxation (Ignarro, 1990;Nakahara et al, 2002;Gao et al, 2004). Nitric oxide (NO), a potent vasodilator in the pulmonary circulation, is important in the transition of the pulmonary circulation from fetal to postnatal life.…”
Section: Cyclic Nucleotides and Pafr-mediated Effectsmentioning
confidence: 99%
“…cAMP production is linked to ␤-adrenergic receptor-mediated activation of adenylyl cyclase (Gilman, 1995;Milligan and Kostenis, 2006). Inhibition of cGMP-and cAMP-dependent phosphodiesterases can also result in high cellular levels of cGMP and cAMP (Nakahara et al, 2002;Hicks et al, 2005). Although 8-Br-cAMP did not significantly alter PAF binding in hypoxia, inhibition of cAMP/PKA with Rp-cAMPS, obliterated the endogenous cAMP effect and significantly increased PAF binding in hypoxia, suggesting that cGMP and cAMP interact with PAFr after activation of their own receptors.…”
Section: Cyclic Nucleotides and Pafr-mediated Effectsmentioning
confidence: 99%
“…This action leads to increased levels of cGMP and inhibition of tracheal smooth muscle contractility (1). Because these increased levels of cGMP result in a potentiating effect on the antiplatelet function of endothelial cell nitric oxide, AV411 also has been used for cerebrovascular disorders, such as poststroke complications (2).…”
mentioning
confidence: 99%
“…To investigate the mechanisms underlying this interaction, we examined the role of Maxi K + channels in nicorandil-induced relaxations of bovine tracheal smooth muscle, since this channel can be activated through NO-cGMP-dependent mechanisms in several smooth muscle tissues, including tracheal smooth muscle [20,21,22,23,24]. In bovine tracheal smooth muscle, sodium nitroprusside-induced relaxations were greatly attenuated when preparations were precontracted with high K + instead of methacholine, as reported in our previous study [25]. In the current study, we found that the Maxi K + channel inhibitor iberiotoxin exhibited an inhibitory effect on NO donor-induced relaxations.…”
Section: Discussionmentioning
confidence: 85%